Fish Diversity in the Upstreams of Achankovil River. - Vishnu A. S. (KUFOS, 2019)
Abstract-Ichthyofaunal diversity study was carried out at 12 sites in the upstream of undammed Achankovilriver, in its perennial tributary ‘Kallar’ that flows through high elevation zones inside the Achankovil Reserve Forest. Thirty-five species of fishes belonging to 8 orders, 13 families and 27 genera were obtained. Cypriniformes (21) contributed to maximum number of species followed by Siluriformes (5), Anguilliformes (2), Synbranchiformes (2), Anabantiformes (2), Cichliformes (1), Beloniformes (1) and Cyprinodontiformes (1). Bariliusbakeri, Salmostomaboopis and Garrasurendranathanii were the dominant species. Family Cyprinidae contributed 11 species followed by Danionidae (6), Anguillidae (2), Balitoridae (2), Nemacheilidae (2), Bagridae (2), Sisoridae (2), Mastacembelidae (2), Channidae (2), Siluridae (1), Cichlidae (1), Belonidae (1) and Aplocheilidae (1). One species belonged to CR, 5 EN, 3 VU, 2 NT, 21 LC, 1 DD, 2 NE as per IUCN Red List and seven species were endemic to Kerala (EN-K) while 19 were endemic to Western Ghats (EN-WG). Species richness was maximum at site 6 and minimum at site 1 whereas the evenness was maximum at site 3 and lowest in site 7. Highest species diversity was observed in site 11 and lowest in site 1 and the average fish abundance was higher for seine net followed by cast net, mosquito net, gill net, scoop net and hook &line. To the Achankovil upstream fish fauna, 12 species viz., Dawkinsia assimilis, Tor malabaricus, Hypselobarbuskurali, Rasboradandia, Mesonoemacheilusherrei, Channapseudomarulius, Anguilla bicolor, Anguilla bengalensis, Puntiusmahecola, Macrognathusguentheri, Batasiotravancoria and a new species of Balitora were added additionally. The results of the study in comparison with the previous studies revealed that the fish diversity and composition were not altered due to the catastrophic flood happened. Immense catching of fishes during dry season from the streams by damming following the usage of natural herbicidal poisons was found to be the major threat prevailing. Ban on fishing during dry season and strict enforcement of Inland Fisheries Act with penalisation of its violators and creation of awareness among locals on conservation of fish fauna and its habitat are the need of the hour for the conservation of resources.